An empirical study on the impact of learning theory on gamification-based training programs - Praveen Kulkarni; Prayag Gokhale; Yellappa Murthy Satish; Basavaraj Tigadi (Organization Management Journal (OMJ), 2022)
Purpose - This study aims to investigate gamification-based training program through the lens of self-determination theory and in the context of corporate training programs. It integrates the self-determination theory, game elements and learning outcomes in gamified training programs to derive insights. Design/methodology/approach - Data is sourced from software development companies operating in the city of Bangalore in India. It applies the partial least square structural equation modeling to investigate the relationship between the self-determination learning theory and game elements and the impact it has on learning outcomes. Findings - As a precursor to the development of a game-like learning ecosystem, the authors study the perception of trainers and human resource managers toward game-based training programs in the organization. The authors find that game-based learning makes training more engaging, immersive and contextual for the learners. Research limitations/implications - The study is based on a specific sector, i.e. software development companies, and so the results may lack in generalizability. Future research, therefore, may consider other industrial sectors such as manufacturing, banking and telecom to understand the relationship between the constructs. Practical implications - This study provides insights for the trainers, human resource managers and academicians on the effectiveness of gamification-based training programs. It also provides information on how the learning theory can be leveraged to understand gamification-based training programs. Social implications - This work fulfills an identified need of the training industry to understand new methods of training with an aim to improve the learning outcomes among the learners. Originality/value - This study provides a deep understanding on the effectiveness of training tools such as gamified training programs in enhancing and improving the learning outcomes among the learners.
Keywords: 650; Gamification; Gamified; Learning; Psychology; Education